The Prabowo–Gibran 2024 Election campaign strategy from Tan Malaka’s Madilog perspective : Strategi kampanye Prabowo-Gibran pada Pemilu 2024 dalam perspektif Madilog Tan Malaka - Arnis Desgita Eka Putri; Maizia Hariyanti Zahra; Mohammad Rayhan Hidayat; Sayyid Verrel; Sisilia Candra Tridjaja; Fathur Rizqi Ramadhan; Jerry Indrawan (Universitas Airlangga, 2025)
This study analyzes the campaign strategy of Prabowo Subianto and Gibran Rakabuming Raka in the 2024 presidential election through Tan Malaka’s Madilog philosophical framework, aiming to uncover fundamental contradictions between political rationality and contemporary mysticism in Indonesian democracy. By employing a philosophical-critical approach and a hermeneutic method, this research uses the three pillars of Madilog (Materialism, Dialectics, and Logic) as tools for systematic analysis of modern electoral phenomena. The findings reveal that the pair’s electoral success was achieved through strategies diametrically opposed to Madilog’s principles: substantive policy has been replaced by symbolic manipulation, advanced technology is used to perpetuate political irrationality, and a “modern mystical logic” dominates, obscuring the critical thinking of the masses. Paradoxically, the public’s skeptical response to the campaign promises reflects an intuitive application of Madilog’s principles by society, highlighting a gap between the people’s critical awareness and the quality of political discourse among the elite. Keywords: Madilog; Political Communication; campaign; electoral rationality; Prabowo-Gibran